Liposome-based Nanoparticles Encapsulating Vitamin D3 Attenuate IL-6 and TNF-α in a Menopausal Mouse Model - Baskara Wiku Adi Kusuma; Sri Ratna Dwiningsih; Ashon As’adi; Sri Puji Astuti Wahyuningsih (The Prodia Education and Research Institute (PERI), 2025)
BACKGROUND: Vitamin D3 is an essential regulator of immune function, however its bioavailability is limited. Liposomes as nanocarriers can enhance vitamin D3 absorption and delivery, however the application of liposomal vitamin D3 in postmenopausal remains underexplored, particularly in preclinical models. Estrogen deficiency during menopause promotes immune dysregulation and elevates proinflammatory cytokines, including interleukin (IL)-6 and tumor necrosis factor (TNF)-α. This study was conducted to evaluate the effects of liposomal vitamin D3 supplementation on serum vitamin D3, IL-6, and TNF-α levels in an ovariectomy-induced menopausal mouse model.METHODS: Mice were randomly divided into four groups comprising non-surgical control (N), ovariectomized without treatment (D−), conventional vitamin D3-treated (D+), and liposomal vitamin D3-treated (LD). Treatments were administered daily via oral gavage for two months. Serum vitamin D3, IL-6, and TNF-α levels were measured by enzyme-linked immunosorbent assay (ELISA). IL-6 and TNF-α data were analyzed by ANOVA with Duncan’s post-hoc test, while vitamin D3 data were analyzed using the Brown-Forsythe test with Games-Howell post-hoc test (p<0.01).RESULTS: Ovariectomy significantly decreased vitamin D3 levels and increased IL-6 and TNF-α levels in the D− group. Conventional vitamin D3 supplementation (D+) significantly decreased serum vitamin D3 levels and slightly decreased IL-6 and TNF-α levels. Liposomal vitamin D3 (LD3) significantly increased vitamin D3 levels and decreased TNF-α, only slightly decreasing IL-6. Correlation analysis showed a negative association between serum vitamin D3 levels and both cytokines.CONCLUSION: Administration of vitamin D3 liposomes was able to increase vitamin D3 levels and suppress IL-6 and TNF-α towards normal levels. LD3 offers enhanced bioavailability and anti-inflammatory effects, making it a promising therapeutic strategy for managing menopause-associated inflammation and related systemic disorders.KEYWORDS: menopause, liposomal VD3, inflammation, IL-6, TNF-α